Morphology changes and long-term cycling durability of Si flake powder negative electrode for lithium-ion batteries. (20th March 2018) - Haruta, Masakazu; Hioki, Ryuya; Moriyasu, Takashi; Tomita, Akira; Takenaka, Toshio; Doi, Takayuki; Inaba, Minoru
Abstract: Silicon flake powder (Si LeafPowder ®, Si-LP) with the thickness and lateral dimension of 100 nm and 3–5 μm, respectively, demonstrated superior cycle performance as a negative electrode in lithium-ion batteries. A multi-folded layered structure with many voids was spontaneously formed in Si-LP composite electrodes by morphology changes of Si-LP sheets in repeated charge and discharge cycles. The multi-folded layered structure accommodated volumetric changes of the Si active material and prevented exfoliation of the active material from the current collector, which led to the superior long-term cyclability of the Si-LP electrode. The main factor for capacity fading in long-term cycling was a gradual loss of conduction pathways between Si-LP sheets due to the accumulation of electrolyte reduction products in the electrode. The film-forming additives, vinylene carbonate and fluoroethylene carbonate, effectively suppressed the electrolyte decomposition and remarkably improved the cycle performance of the Si-LP electrode. Graphical abstract: Image 1 Highlights: Si LeafPowder ® (Si-LP) negative electrode demonstrated superior cycle performances. The Si-LP resisted cracking and pulverization due to its unique flake shape. A multi-folded layered structure was spontaneously formed in Si-LP composite. The multi-folded layered structure enabled a stable long-term cycle operation.